ASSESSMENT OF THE ADAPTIVE ABILITIES IN JUNIOR SCHOOL STUDENTS USING GAME BIOFEEDBACK TECHNOLOGY - Ye. N. Danilenko; O. A. Jafarova; K. G. Mazhirina (Бюллетень сибирской медицины)
In this study we selected 3 basic types of the adaptive behavior of the junior school students (n = 80) using a comparative analysis of the psychological and psycho-physiological characteristics in the course of game biofeedback. As a result of training the emotional state of the students normalized and psycho   physiological tension decreased. The ADHD and frequently ill students also got a positive outcome after training.